Imaging Review of Procedural and Periprocedural Complications of Central Venous Lines, Percutaneous Intrathoracic Drains, and Nasogastric Tubes - Hamdan Al-Jahdali; Klaus L. Irion; Carolyn Allen; Daniel Marafiga de Godoy; Ali Nawaz Khan (Pulmonary Medicine)
Placements of central venous lines (CVC), percutaneous intrathoracic drains (ITDs), and nasogastric tubes (NGTs) are some of the most common interventional procedures performed on patients that are unconscious and in almost all intensive care/high dependency patients in one form or the other. These are standard procedures within the remit of physicians, and other trained health professionals. Procedural complications may occur in 7%–15% of patients depending upon the intervention and experience of the operator. Most complications are minor, but other serious complications may add significantly to morbidity and even mortality of already compromised patients. Imaging findings are the key to the detection of misplaced lines, and tubes and their prompt recognition are vital to avoid harm to the patient. It is, therefore, pertinent that healthcare professionals who perform these procedures are familiar with imaging complications of these procedures. Here, we present the imaging characteristics of procedural complications.